ECO-BALANCE OF SOIL TILLAGE SYSTEMS TO RESTORE AND INCREASE SOIL FERTILITY - Chaika, T. O.; Yasnolob, I. O.; Gorb, O. O.; Lotysh, I. I.; Bereznytskyi, Yev. V. (Scientific Progress & Innovations, 2019)
The article highlights the current state of farm lands in Ukraine, which are affected by erosion, degrada-tion, loss of fertility and moisture. As a result of irresponsible attitude of owners and leaseholders, drying up and desertification of territories, soil dying takes place. The expediency of conducting urgent measures to prevent and eliminate erosion processes, increase their deflation stability, reduce acidity and restore humus is substantiated. It is mentioned that the effectiveness of these measures depends first and foremost on the responsible attitude of landowners and land users, since in the pursuit of super profits the exploitation of farm lands is devastating. The priority measure to restore and improve soil fertility in Ukraine is the using of appropriate systems of farm land tillage. Foreign and Ukrainian experience of using basic soil tillage sys-tems (plow, minimal and zero) was investigated and their peculiarities were determined. This enabled to characterize the advantages and disadvantages of each soil tillage method, which allow assess their impact on the condition and composition of soils, the quality of farm products and influence on the natural environ-ment, which determines their urgency and the necessity for agricultural producers, the impact on soil fertili-ty. The criteria of estimating soil tillage systems on the principles of sustainable development according to agronomic, economic, social and ecological directions were suggested. The necessity of introducing such soil tillage systems, the using of which enables to increase the productivity of farm machinery and used re-sources, reduce the incurred production expenses and ecological loading on the environment, and ensure long-term development of agricultural production without losing product quality, was proved.